International Tax Cooperation and Capital Mobility. - FitzGerald, V (United Nations Economic Commission for Latin America and the Caribbean, 2002)
The international mobility of capital and the geographical dispersion of firms have clear advantages for the growth and modernization of Latin America and the Caribbean, but they also pose great challenges. Modern principles of capital taxation for open developing economies indicate the need to find the correct balance between the encouragement of private investment and the financing of social infrastructure, both of which are necessary for sustainable growth. This balance can be sub-optimal when countries compete for foreign investment by granting tax incentives or applying conflicting principles in determining the tax base. The fiscal authorities of the region could obtain a more equitable share of capital tax revenue, without depressing investment and growth, through more effective regional tax rules, double taxation treaties, information sharing and treatment of offshore financial centres along the lines already promoted for OECD members.